1930
DOI: 10.1084/jem.51.6.831
|View full text |Cite
|
Sign up to set email alerts
|

Biological Studies of the Tubercle Bacillus

Abstract: The recent advances in the study of the other bacteria with application to the dissociation phenomenon, have been applied in the study of acid-fast organisms. For some time, we have realized that the term "dissociation" as employed at present, is not adequate to explain the instability and subsequent variation which occur in cultures. But for uniformity of bacteriological nomenclature, we have adopted the term until a better one is coined. In describing the "R" and "S" colonies, we have had to depart somewhat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1933
1933
1989
1989

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Dissociation technique as previously described and successfully used in the dissociation of avian, bovine, and B.C.G. cultures of tubercle bacilli was applied in this study (1).…”
Section: -M'ental Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Dissociation technique as previously described and successfully used in the dissociation of avian, bovine, and B.C.G. cultures of tubercle bacilli was applied in this study (1).…”
Section: -M'ental Datamentioning
confidence: 99%
“…Procedure.--Blood studies were made on the variant groups of two series of guinea pigs (1,4), and one series of rabbits (10).…”
Section: Hematologymentioning
confidence: 99%
“…The virulence was not reported. In later studies (18,19,27), however, the colonies designated as S were low, spreading, granular, with somewhat irregular borders (27,Figs. 3 and 4).…”
mentioning
confidence: 91%
“…Petrott and his associates were the first to study the dissociation of tubercle bacilli. They demonstrated two or more types of colonies in cultures of human (15,18,19,27), attenuated bovine (BCG) (16,17), virulent bovine (18,19), and avian tubercle bacilli (18)(19)(20). Four colony types were differentiated and stabilized in the case of the avian bacilli.…”
mentioning
confidence: 99%
“…This level of susceptibility is much less than that reported for either rhesus monkeys or Hartley guinea pigs, both of which can be killed by an inoculum of <5 virulent tubercle bacilli (94,105). Initial studies carried out in outbred Hartley guinea pigs had indicated that they could be killed by a single viable unit of M. tuberculosis H37Rv (158). However, this level of virulence is difficult to maintain in laboratory cultures, and later studies indicate that the median lethal dose for this strain is now around 5 x 105 (52,187 Despite a great deal of study, we know very little about the virulence antigens associated with M. tuberculosis or the way in which they antagonize the normal host defenses (63).…”
Section: Virulence Of Mycobacteria For Humans and Experimental Animalsmentioning
confidence: 91%